Farm animal biodiversity conservation activities in Europe under the framework of Agenda 2000 - Giovanni Signorello; Gioacchino Pappalardo (Fondazione Eni Enrico Mattei (FEEM), 2002)
In this paper we examine the content of farm animal biodiversity conservation measurescurrently under implementation in the European Union (EU), as a result of the application of EC Regulations 1257/99 and 1750/99. We surveyed 69 Rural Development Plans (RDPs) set up in EU Member States. Our analysis focuses on six livestock mammalian species: asses, cattle, goats, horses, pigs, and sheep The starting point for our investigation is the Domestic Animals Diversity-Information System (DAD-IS) FAO database which monitors the status of breeds in the world. We compare breeds included in the DAD-IS FAO database with breeds covered by the various RDPs. The analysis highlights that many breeds at risk of extinction according to FAO are not included in the RDPs. The analysis also indicates that the main efforts of the RDPs are devoted to preserving local cattle and sheep breeds. As concerns the financial aspects of livestock biodiversity measures, we note that the payments offered to farmers do not take into account the different probabilities of extinction associated with each breed in each country. Furthermore, we observe that payments do not meet all of the relevant criteria stated in the EEC Regulations. In many cases, we observe that, in spite of the Union's support to farmers, it still remains unprofitable to rear local breeds. These anomalies suggest the need for a revision of the current EU supporting measures related to the conservation of livestock biodiversity. Finally, by using FAO indicators on the current population size of each breed, we estimate the level of expected public expenditure necessary to ensure the upgrading of breeds from their
Keywords: Q18; Q20; 330; Farm animal biodiversity; Agenda 2000; Rural Development Plans; Artenvielfalt; Tierzucht; EU-Agrarpolitik; EU-Staaten